Democracia em vertigem e não vai ter golpe!: acontecimento e modos de subjetivação política no Brasil contemporâneo - Andrade, Michel Renan Rodrigues de (2023)
With the aim of analyzing the tactics and strategies that produce modes of political subjectivation based on the discursive practices engendered in disputes over the event in contemporary Brazilian politics, this work analyzes two contemporary materialities that narrated and sought to constitute a conceptual domain over the event of the impeachment of former president Dilma Rousseff: the films Democracia em Vertigem (2019), by Petra Costa and Não Vai ter um coup! (2019), by Alexandre dos Santos and Fred Rauh. Much is said in current political analyzes in Brazil about a supposed dispute of narratives as the current form of struggle between different political spectrums. Our research is based on a premise that problematizes this notion. In order to analyze the emerging modes of subjectivation in political struggles today, we start from the hypothesis that the dispute is not over narratives, but rather over events - an ideal atmosphere for controlling discourse and constituting an order capable of producing perceptions. , affections and practices that form modes of subjectivation in action in power relations. The two documentaries produced from antagonistic political perspectives construct notions that conflict with the impeachment of President Dilma Rousseff in 2016. The speeches produced circulate in the Brazilian public sphere and are important elements for current modes of political subjectivation. Given this, with documentary cinema in the form of these two films as materialities and under a lens of Foucauldian tools, we carry out an analysis of the relationship between cinema language and politics as a strategic form for the production of modes of subjectivation; we discuss concepts from the perspective of Foucault and Bill Nicholls in relation to the history of cinema and documentaries and, then, performing a decoupage of the films, we identify the main enunciative and affective categories and analyze the processes that create meanings and affections in these relationships . With this, we understand cinema as a tactic of power struggles, crossed by strategies of the media device that is important for the formation of the political subject. We realize that the dispute over the event produces modes of subjectivation linked to current sociopolitical struggles. Using the discourse analysis method, we observed that the emotions that emerged are preponderant factors in the constitution of subjects. If on the right side we have indignation emerging from the fight for democracy under violent and vigilante affections, attacks and calls for the destruction of the enemy, on the left, the indignation arises from a hopeful resistance, which under the feeling of injustice, melancholy and vertigo mobilize security in the discourses formed by statements more rooted in knowledge, memory and the fight against the contradictory. We consider that the dispute over the event does not occur only through narrative, since this is done as a tactic and also through strategies that are crossed by several important devices for the constitution of subjects.